Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/elan.202200194
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Ion‐selective Electrode with a Sensitive Ion‐to‐Electron Transducer Composed of Porous Laser‐induced Graphene and MoS2 Fabricated by One‐step Direct Laser Writing

Abstract: In this study, an ion‐selective electrode with a sensitive ion‐to‐electron transducer composed of porous laser‐induced graphene (LIG) and MoS2 (LIG‐MoS2/ISE) was fabricated to measure the potassium ion concentration in a greenhouse nutrient solution for soilless culture. Additionally, a more effective and low‐cost method was proposed for the large‐batch production and manufacture of potassium ion‐selective electrodes (K+‐ISEs) using the direct laser writing technique, which differs considerably from existing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…[319] The first to synthesizing such composite materials is the deposition of a metal precursor phase over the graphitizable substrate, using solution processing approaches. [170,[320][321][322][323][324] A second approach is the formulation of liquid composite precursors, that present both the organic, LIG precursor phase and the metal precursor simultaneously. [325][326][327] Using both strategies, LIG-based composites with metallic elements have been produced, using the thermal laser stimulus to simultaneously graphitize the carbon organic precursor and reduce or oxidize the metallic precursor.…”
Section: Dlw Synthesis Of Hybrid and Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[319] The first to synthesizing such composite materials is the deposition of a metal precursor phase over the graphitizable substrate, using solution processing approaches. [170,[320][321][322][323][324] A second approach is the formulation of liquid composite precursors, that present both the organic, LIG precursor phase and the metal precursor simultaneously. [325][326][327] Using both strategies, LIG-based composites with metallic elements have been produced, using the thermal laser stimulus to simultaneously graphitize the carbon organic precursor and reduce or oxidize the metallic precursor.…”
Section: Dlw Synthesis Of Hybrid and Composite Materialsmentioning
confidence: 99%
“…Besides metal and metal oxide embedded phases for LIG-based composite synthesis, concurrent synthesis of other semiconductor materials has been explored, including chalcogenides such as hafnium diselenide [323] and molybdenum disulfide. [324] Based solely on carbonization mechanisms, the writing of LIG doped with several carbides has also been explored. Molybdenum carbide nanostructures embedded in conductive carbon have been reported using paper substrates [257,258] by soaking the cellulose matrix with molybdenum metal ions.…”
Section: Dlw Synthesis Of Hybrid and Composite Materialsmentioning
confidence: 99%
“…These results confirmed that the Co3O4 NPs were successfully used as a transducer material. EIS measurements were performed over frequencies ranging from 10 Hz to 10 6 Hz with an open-circuit voltage of 0.358 V and an excitation amplitude of 0.005 V. Figure 6b depicts the equivalent circuit used to fit the resulting Nyquist plots, in which R b , R ct , R s , C dl , CPE, and W represent the bulk membrane resistance together with the contact resistance between the underlying conductor and the ISM, the charge-transfer resistance, the solution resistance, the double-layer capacitance, the constant phase angle element, and the Warburg impedance, respectively [41]. The R ct values of the SPE (red points) were approximately 0.72 kΩ.…”
Section: Chronopotentiometric Testmentioning
confidence: 99%